Efeitos de um procedimento informatizado e aplicado de forma remota e síncrona na leitura e escrita de sentenças para crianças em idade escolar - Silva, Natany Ferreira (Universidade Federal de São Carlos, 2021)
Reading and writing repertoires are fundamental for learning more complex academic skills and enable individuals to be more autonomous. Behavior analysis has demonstrated success in applying the equivalence-based instruction (EBI) model of sentence reading instruction to children with learning disabilities. This study replicated and evaluated the effects of a computerized equivalence-based instruction (EBI) procedure on reading and writing in school-aged children. Six children, from three Brazilian states, aged from 8 to 10 years old, attented enrolled in the 2nd and 4th grades of elementary school participated in the study. For recruitment and selection of participants, the research was advertised in different messaging apps groups. The researcher made the invitation through a message published in the groups, informing about the research, the objective, the procedure, and the telephone contact. The participants were indicated by their own family members or by third parties who had contact with the children. The criteria for participating in the research were: having a maximum of 60% of correct answers in reading sentences in the Reading and Writing Network Assessment; having a computer and internet access at home; presenting behaviors such as remaining seated for the research activities, paying attention to the tasks and following the researcher's instructions and questioning her if there were doubts, and availability to participate at least three times a week in the online activities. Pre- and post-intervention and multiple probes between teaching matrices designs were employed. The teaching consisted of EBI and on the organization of stimuli in matrices, and it was conducted via a remotely and synchronously computerized procedure. Three teaching matrices were used, respecting a sentence complexity hierarchy. In the teaching sessions, the three diagonal sentences from each of the three matrices were used, totaling nine teaching sentences. For the evaluation of recombinative generalization, the nine trained sentences, six intra-matrix generalization sentences and 12 stimuli from the recombination of the elements of the three matrices (inter-matrix generalization) were used, being a total of 27 sentences in the study. The phases sequences were: 1) Initial evaluation: Reading and Writing Network Assessment, Syntactic Awareness Test and Generalization Evaluation: Typed Dictated Sentence Test; 2) Teaching the relation dictated sentence-figure (AB) and the relation dictated sentence-written sentence construction (AE); 3) Probes between the matrices; and 4) Final evaluation: Initial evaluation: Reading and Writing Network Assessment, Syntactic Awareness Test and Generalization Evaluation: Typed Dictated Sentence Test. Participants strengthened or learned the taught relations AB and AE for the taught matrices. In the assessed relations, they also strengthened and/or showed emergence of relations not directly taught. Overall, participants demonstrated increased reading comprehension repertoire (BC and CB relations) for the taught and recombined sentences, as well as increased correct sentence reading responses (CD). The data showed that the teaching conditions applied remotely and synchronously contributed to the learning of sentence reading for school-age children. Investment in studies that aim seek to develop computerized teaching procedures, especially in the pandemic context, may contribute to the learning of students in the literacy process.
Effects of a computerized procedure and remotely applied and synchronously in the reading and writing of sentences for school-age children
Keywords: Leitura; Escrita; Sentenças; Equivalence based instruction; Ensino por matrizes; COVID-19; Reading; Writing; Sentences; Children; Matrix training; Crianças; CIENCIAS HUMANAS::EDUCACAO